Pelaksanaan Kebijakan Penyanderaan Pajak (Gijzeling) Dilihat Dari Perspektif Hak Asasi Manusia - Sirait, Resmaya Agnesia Mutiara (Faculty of Law, Universitas Pattimura, 2020)
Tax is a source of income for a country, the use of tax money to finance all state expenditures and financing state development projects. Tax collection is carried out by the state to taxpayers or tax bearers. The current monetary crisis makes many taxpayers who do not obey in paying taxes. So the government must create a new mechanism that aims to help forcibly for taxpayers who do not obey the law. One such mechanism is the forced institution of body (gijzeling). In establishing gijzeling institutions, there are things that must be considered and considered, namely the legal, justice and humanitarian needs (Human Rights), because basically these institutions contain elements of deprivation of liberty. This study aims to analyze how the institution of forced agency (gijzeling) is implemented and how the implementation of tax hostage policy (gijzeling) is seen from the perspective of Human Rights. From the results of the study, it is known that the enforced implementation of the body can be carried out if other administrative legal activities are proven and the tax guarantor has arrears a tax payment of Rp 100,000,000-, and viewed from the perspective of human rights taking a tax (gijzeling) is basically a deprivation of a person's right to independence, but related to the tax guarantor who has no good intention, gijzeling can be applied.